Ethics in Qualitative Research: A Response-able Intra-action - Shehr Bano Zaidi (University of Chitral Journal of Linguistics and Literature, 2024)
This study attempts to re/configure the regulation of qualitative research by ethics systems practiced in Pakistan by contextualizing it in international practices. Barad’s ethico-onto-epistemological approach facilitates a nuanced understanding of issues through its affirmative engagement with the other. While acknowledging the Pakistani scientific community’s awareness of the importance of ethics, a need for separate ethics boards for qualitative research is impressed upon. Some problematic terms like ‘research involving humans’ and practices like using ready-made restrictive templates have to be re/thought. The study also suggests drawing upon creative literature like novels, dramas, etc. in research proposals as it can help convince committees about the importance of researching lesser-studied topics, especially those which are related to a region’s or society’s contentious past and present. Finally, the response-able role of university faculty associations is emphasized.